Application of SAVI Model on Addition and Subtraction Material In Class 2 MI to Improve Student Learning Outcomes - Khasanah, Mareta Uswatun; Sari, Kanthi Pamungkas (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
This study aims to determine the learning outcomes of grade II students of MI Muhammadiyah Jagalan, Salam District, Magelang Regency using the SAVI (somatic, auditory, visual, intelectuall) learning model based on the ravine board (addition and subtraction) in math learning. The method used in this research is classroom action research, with a sample size of 12 students with sampling using pre-test and post-test. Used as research instruments are teaching modules, observation sheets, and documentation. The results showed the use of the SAVI learning model, giving an influence on student abilities and a significant increase in student learning outcomes in addition and subtraction math lessons. It can be seen in the first cycle percentage of 55.5% and achieved a successful increase in the implementation of the second cycle action of 77.7%.  The use of the abyss board can increase students to be more active in participating in the learning process, such as daring to ask questions, being able to practice with the abyss board media, being able to present the results of work in front of the class, and being able to work together with the group.